A curcumin direct protein biosensor for cell‐free prototyping. Issue 2 (18th August 2022) - Kennedy, Agata; Griffin, Guy; Freemont, Paul S.; Polizzi, Karen M.; Moore, Simon J.
Abstract: In synthetic biology, biosensors are routinely coupled with a gene expression system for detecting small molecules and physical signals. We reveal a fluorescent complex, based on the interaction of an Escherichia coli double bond reductase ( Ec CurA), as a detection unit with its substrate curcumin—we call this a direct protein (DiPro) biosensor. Using a cell‐free synthetic biology approach, we use the Ec CurA DiPro biosensor to fine tune 10 reaction parameters (cofactor, substrate, and enzyme levels) for cell‐free curcumin biosynthesis, assisted through acoustic liquid handling robotics. Overall, we increase Ec CurA‐curcumin DiPro fluorescence within cell‐free reactions by 78‐fold. This finding adds to the growing family of protein–ligand complexes that are naturally fluorescent and potentially exploitable for a range of applications, including medical imaging to engineering high‐value chemicals.